Human Leukocyte Antigen Profile Predicts Severity of Autoimmune Liver Disease in Children of European Ancestry. Issue 4 (21st June 2021) - Ma, Yun; Su, Haibin; Yuksel, Muhammed; Longhi, Maria Serena; McPhail, Mark J.; Wang, Pengyun; Bansal, Sanjay; Wong, Guan‐Wee; Graham, Jonathon; Yang, Li; J Thompson, Richard; Doherty, Derek G.; et al.
Abstract : Background and Aims: Genetic predisposition to autoimmune hepatitis (AIH) in adults is associated with possession of human leukocyte antigen (HLA) class I ( A*01,   B*08 ) and class II ( DRB1*03,   ‐04, ‐ 07, or  ‐13 ) alleles,  depending on geographic region. Juvenile autoimmune liver disease (AILD) comprises AIH‐1, AIH‐2, and autoimmune sclerosing cholangitis (ASC), which are phenotypically different from their adult counterparts. We aimed to define the relationship between HLA profile and disease course, severity, and outcome in juvenile AILD. Approach and Results: We studied 236 children of European ancestry (152 female [64%], median age 11.15 years, range 0.8‐17), including 100 with AIH‐1, 59 with AIH‐2, and 77 with ASC. The follow‐up period was from 1977 to June 2019 (median 14.5 years). Class I and II HLA genotyping was performed using PCR/sequence‐specific primers. HLA  B*08, ‐ DRB1*03, and the  A1‐B8‐DR3  haplotype impart predisposition to all three forms of AILD. Homozygosity for  DRB1*03  represented the strongest risk factor (8.8). HLA  DRB1*04,  which independently confers susceptibility to AIH in adults, was infrequent in AIH‐1 and ASC, suggesting protection; and DRB1*15 (DR15) was protective against all forms of AILD. Distinct HLA class II alleles predispose to the different subgroups of juvenile AILD:  DRB1*03  to AIH‐1,   DRB1*13  to ASC, and  DRB1*07  to AIH‐2. Possession of homozygous  DRB1*03 or of DRB1*13 is associated with fibrosis at disease onset, and possession of these two genes in addition to  DRB1*07  is associated with a more severe disease in all three subgroups. Conclusions: Unique HLA profiles are seen in each subgroup of juvenile AILD. HLA genotype might be useful in predicting responsiveness to immunosuppressive treatment and course.